Capacity building for guidance and counseling teachers in coastal schools through narrative counseling to enhance students’ life meaning - Wijaya Rasman Sastra; Suherman La Ode Achmad; Manan Manan; Tarno Tarno; Gawise Gawise; Jannah Nur; Rajab Gusrianda Bin (BIO Web of Conferences)
This study aims to develop and evaluate a capacity-building framework for guidance and counseling teachers in coastal schools through the integration of narrative counseling approaches. Many coastal students face psychosocial and educational disadvantages due to limited access to trained counselors and culturally relevant guidance models. Grounded in a contextual needs analysis and validated by six experts, the proposed framework combines theoretical principles with localized strategies that support identity development and life meaning construction. The study involved 34 teachers randomly assigned to experimental and control groups. Both received narrative counseling training, but only the experimental group implemented it in practice. Competency improvement was measured using pre- and post-tests, analyzed through normalized gain (N-Gain) scores, independent t-tests, and effect size calculations. Results showed a significantly higher mean N-Gain in the experimental group (0.7565) compared to the control (0.2971), with a large effect size (Cohen’s d = 2.194). Qualitative feedback from teachers, students, and experts further confirmed the framework’s practical relevance and cultural fit. The findings suggest that structured narrative-based training can meaningfully enhance counseling competencies, especially in underserved coastal contexts. The framework offers a replicable model for counselor professional development and contributes to the discourse on narrative identity and student well-being.